1996
DOI: 10.1159/000217961
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Double-Stranded RNA-Dependent Protein Kinase (p68) in Human Breast Tissues

Abstract: P68 is a potent inhibitor of protein synthesis in virally infected cells and has been suggested to function in noninfected cells as a tumor suppressor gene. We have previously demonstrated that p68 expression correlates directly with cellular differentiation and inversely with proliferative activity in normal epithelium and in several human tumor systems. In order to determine the role of p68 in human breast cancer, we utilized immunohistochemistry and mapped the expression of p68 in tissue from 200 breast bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 8 publications
3
35
0
Order By: Relevance
“…The chromagen staining in the carcinoma cells is blocked by PKR protein indicating that the staining is speci®c for PKR (data not shown). These results indicate that PKR expression in the breast carcinoma and the nontransformed cell lines are indeed similar to that reported in the carcinoma and the normal epithelial tissues from patients (Haines et al, 1996). We therefore proceeded to use the cell lines for biochemical analysis of the role of PKR in breast cancer.…”
Section: Immunohistochemical Detection Of Pkr In Mammary Carcinoma Cesupporting
confidence: 69%
See 2 more Smart Citations
“…The chromagen staining in the carcinoma cells is blocked by PKR protein indicating that the staining is speci®c for PKR (data not shown). These results indicate that PKR expression in the breast carcinoma and the nontransformed cell lines are indeed similar to that reported in the carcinoma and the normal epithelial tissues from patients (Haines et al, 1996). We therefore proceeded to use the cell lines for biochemical analysis of the role of PKR in breast cancer.…”
Section: Immunohistochemical Detection Of Pkr In Mammary Carcinoma Cesupporting
confidence: 69%
“…An earlier immunohistochemical analysis of breast cancer tissues had indicated that PKR was expressed at high levels in carcinoma tissues as compared to the normal mammary ductal epithelial cells (Haines et al, 1996). To determine whether similar results pertain in cell lines, we performed immunohistochemical analysis on the cell lines derived from breast carcinoma and nontransformed cells.…”
Section: Immunohistochemical Detection Of Pkr In Mammary Carcinoma Cementioning
confidence: 97%
See 1 more Smart Citation
“…For example, it was previously shown that human invasive ductal breast carcinomas and several human breast tumor cell lines contain elevated levels of PKR compared with non-malignant breast cells. 30,31 However, the PKR-eIF2a phosphorylation SubG1: 64% SubG1: 44% Figure 4 Phosphorylation of eIF2a protects cells from doxorubicin-induced death. (a) eIF2a S/S and eIF2a A/A MEFs were left untreated (con) or treated with 1 mM doxorubicin (dox) for the indicated time periods.…”
Section: Discussionmentioning
confidence: 99%
“…In IL3-dependent cells the withdrawal of IL3 results in the phosphorylation of RAX, a protein activator of PKR and subsequent eIF2a phosphorlyation, inhibition of protein synthesis and apoptosis di erent human tumors and tumor cell lines (Haines et al, 1996;Zhou et al, 1998;Shimanda et al, 1998). Human invasive ductal breast carcinomas have high levels of PKR and in several breast carcinoma cell lines PKR levels are high compared to those found in lines derived from normal breast (Haines et al, 1996;Savinova et al, 1999). Despite high levels, the activity of PKR from the carcinoma cells is attenuated although it remains capable of binding dsRNA.…”
Section: Pkr Viral Mediated Apoptosis and Heat Shockmentioning
confidence: 99%